Efektivitas Penggunaan Anestesi Regional terhadap Pengurangan Nyeri Pasca Operasi - Polanunu, M. Akbar AliPolanunu (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Postoperative pain is a major problem for patients undergoing surgery. Suboptimal pain management can lead to physiological and psychological complications, delay recovery, and reduce the patient's quality of life. One method of pain management is the use of regional anesthesia, which has the advantage of reducing pain intensity and reducing the need for additional analgesics. Objective: This study aimed to determine the effectiveness of regional anesthesia in reducing postoperative pain compared to general anesthesia. Methods: This study used a quasi-experimental design with a post-test only control group design. A sample of 60 elective surgery patients was divided into two groups: regional anesthesia (n=30) and general anesthesia (n=30). Pain intensity was measured using a Visual Analog Scale (VAS) at 6 and 12 hours postoperatively. Data were analyzed using an independent t-test. Results: The study showed that the average VAS score in the regional anesthesia group was lower than that in the general anesthesia group, both at 6 hours (2.8 ±1.1 vs. 5.4 ±1.5) and 12 hours (3.1 ±1.2 vs. 5.9 ±1.7) postoperatively. A t-test showed a significant difference (p < 0.05) between the two groups. Conclusion: Regional anesthesia has been shown to be effective in reducing postoperative pain intensity. This method can be considered as a primary strategy for perioperative pain management to accelerate patient recovery.